Democratization and real exchange rates - Benjamin Furlan; Martin Gächter; Bob Krebs; Harald Oberhofer (FIW - Research Centre International Economics, 2013)
This paper empirically assesses how democratization affects real exchange rates. By doing this, we combine so far separated strands of the economic literature and argue that democratization reduces currency undervaluation leading to a real exchange rate appreciation. We test this hypothesis empirically for a sample of countries observed from 1980 to 2007 by combining a difference-in-difference (DID) approach with propensity score matching (PSM) estimators. Our results reveal a strong and significant finding: democratization causes real exchange rates to appreciate. Consequently, the ongoing process of democratization observed in a few Arabic and Moslem countries is likely to reduce exchange rate distortions.
Keywords: C21; C23; F02; F31; F59; N20; 330; Real exchange rates; democratization; difference-in-differencesestimator; matching estimators